The Role of the Mining Company Corporate Social Responsibility and the Issue of the Weda Bay Sea Ecosystem Environmental Health - Faisal Faisal; Jamal HI Arsyad; Rusdin Alauddin (Journal of Global Pharma Technology, 2020)
Purpose: This research is aimed to know the management of the Corporate social responsibility carried out by the PT. TEHT in Central Halmahera and also to know how the ideal mining management activity is which is based on environmental management and protection. Method: The method used is the empirical research method using the statute approach and the case approach. Result: The inventarization results of field study are analyzed to obtain the conclusion, then it is analyzed using the integrative and conceptual method of analysis which is courced from the primary and the secondary data. The problem which is analyzed in this research departs from when PT. TEHT disposed ore in the Central Halmahera sea, which directly brings loss to the sea ecosystem of the Weda Bay. This is because the responsibility of a company has direct impact to the social and the environmental activities. It is manifested in the form of behaviors and activities which should be in line with the sustainable development and the social welfare. Also, the legal regulations are integrated with the principle of sustainable environment protection and management. Conclusion: The company should be aware of the social and the environmental health dimensions which become the processing location of the mining materials. The Weda Bay experienced environmental destruction due to mining and it becomes an unhealthy environment.